Iron Homeostasis and Trypanosoma brucei Associated Immunopathogenicity Development: A Battle/Quest for Iron. (18th May 2015) - Stijlemans, Benoit; Beschin, Alain; Magez, Stefan; Van Ginderachter, Jo A.; De Baetselier, Patrick
Abstract : African trypanosomosis is a chronic debilitating disease affecting the health and economic well-being of developing countries. The immune response during African trypanosome infection consisting of a strong proinflammatory M1-type activation of the myeloid phagocyte system (MYPS) results in iron deprivation for these extracellular parasites. Yet, the persistence of M1-type MYPS activation causes the development of anemia (anemia of chronic disease, ACD) as a most prominent pathological parameter in the mammalian host, due to enhanced erythrophagocytosis and retention of iron within the MYPS thereby depriving iron for erythropoiesis. In this review we give an overview of how parasites acquire iron from the host and how iron modulation of the host MYPS affects trypanosomosis-associated anemia development. Finally, we also discuss different strategies at the level of both the host and the parasite that can/might be used to modulate iron availability during African trypanosome infections.